2013
DOI: 10.1111/j.1755-3768.2013.4676.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of refractive error and axial length on retinal vessel geometric characteristics

Abstract: Purpose To evaluate the influence of refractive error and axial length (AL) on retinal vascular network geometry measurements in an adult Asian population. Methods This was a population‐based, cross‐sectional study on 2882 persons with diabetes in the Singapore Malay Eye Study (SiMES). Spherical equivalent refraction (SE) was assessed using an autokeratorefractometer and subjective refraction. AL was measured by IOL Master. Retinal vascular caliber, tortuosity, and branching characteristics were quantified fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Recent studies have demonstrated an association between narrowing of retinal arteriolar caliber and spherical equivalent using retinal photography and measurement of retinal vascular calibers and suggested that myopia might have an effect on retinal microvasculature (20,22). It is known that refractive errors are due to elongation of the eyeball are typical in myopic subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated an association between narrowing of retinal arteriolar caliber and spherical equivalent using retinal photography and measurement of retinal vascular calibers and suggested that myopia might have an effect on retinal microvasculature (20,22). It is known that refractive errors are due to elongation of the eyeball are typical in myopic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…By the increase of SE in myopic subjects, the axis also elongates since the myopic subjects have larger bulbi and the axial length and refraction share common genes in their etiology (5,17). This mechanical stretching and thinning of the choroid and retinal pigment epithelium with accompany with concomitant vascular and degenerative changes such as reduction of retinal blood flow velocity and decreased retinal vascular caliber and retinal vessel geometry (20,21,22,34,35). According to our finding, this volume-pressure association has no effect on the investigated systemic hemodynamic parameters, neither on augmentation index (peripheral vascular resistance) nor on systemic arterial stiffness (PWV) and other pressure values measured by oscillometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in ocular shape, as it occurs for example in myopia, are often associated with vascular abnormalities [5,34,42] and with higher risks of severe ocular conditions, such as glaucoma [18,30], retinal detatchment [32,50] and maculopathy [17,27]. Architectural changes in the retinal vasculature are also often associated with ocular diseases, including glaucoma [22,29,46,48], diabetic retinopathy [9,8,24] and myopia [16,31].…”
Section: Introductionmentioning
confidence: 99%
“…Degeneration of retinal vessel walls and changes in their elastic properties have been identified to be major causes of vessel tortuosity (Azegrouz et al;. The duration of diabetic disease has a strong effect on changes in vessel tortuosity (Lim et al;Sasongko et al;.…”
Section: Introductionmentioning
confidence: 99%